Psychological Obstacles of a Da'i in Giving Advice According to the View of the Al-Quran - Mohamad Taufik (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
A preacher has a duty to invite goodness with sincere intentions and without expecting anything from the object of his preaching, besides that the preacher must also believe in himself and his ability to provide good and useful advice for others. As a preacher, of course, we must also provide a good example and show that what we teach is something that is done in everyday life. That way, people will find it easier to follow what we convey. However, in reality there are several psychological obstacles that are often experienced by preachers in inviting goodness and not everyone is easy to invite to goodness, therefore this article will discuss what are the psychological obstacles of a preacher in advising and trying to provide solutions to these problems.